Upaya Menghadapi Menarche dengan Meningkatkan Pengetahuan Remaja Putri Melalui Menstrual Hygiene Management Comic Book Di Pondok Pesantren Hidayatullah - Usman, Hastuti; Tondong, Henrietta Imelda; Kuswanti, Febti (Universitas Nusantara PGRI Kediri, 2022)
Menstrual hygiene management is the management of hygiene and health when women are menstruating which needs to be considered because during menstruation the uterus is very easily infected. Without proper hygiene management during menstruation, women have a higher risk of being infected with diseases, especially diseases related to reproductive organs. This Community Service activity at the Hidayatullah Islamic Boarding School, Tondo Village, Palu City aims to improve the knowledge and skills of young women in dealing with menarche through Menstrual Hygiene Menagent Comic Book at the Hidayatullah Islamic Boarding School. The methods used in this community service are lectures, discussions and demonstrations. The lecture method is used when providing information regarding preparation for menarche by explaining Hygiene Menagent Comic Book. The discussion method was used during the question and answer session and the practice of preparing for menarche. The demonstration method is used when practicing how to deal with menarche. The ultimate goal of this activity is to provide open insight and additional knowledge about the importance of personal hygiene management during menstruation for young women so that it is hoped that every school can provide Menstrual Hygiene Management Comic Books as a basis for efforts to increase young women's knowledge about dealing with menarche.